Starch and fiber intake effects on energy metabolism, growth, and carapacial scute pyramiding of red-footed tortoise hatchlings (Chelonoidis carbonaria) - Mendoza, Pierina [UNESP]; Furuta, Camila [UNESP]; Garcia, Beatriz [UNESP]; Zena, Lucas A.; Artoni, Silvana [UNESP]; Dierenfeld, Ellen S.; Bícego, Kênia C. [UNESP]; Carciofi, Aulus C. [UNESP] (Elsevier, 2022)
Tortoise husbandry includes reports of excessive growth and carapace pyramiding, although triggers still remain to be fully elucidated. Juvenile red-footed tortoises (Chelonoidis carbonaria) were fed with two different diets, one high in fiber (HF; 14.2% crude fiber; 39.2% neutral detergent fiber, NDF; dry matter basis, DMB) and one high in starch (HS; 27.7% DMB), to assess effects on energy metabolism, nutrient digestibility, and growth. A total of 20 hatchlings (10 per diet) were used to evaluate: apparent digestibility coefficients (Da) of nutrients and gross energy (GE), passage times at 5 and 11 months of age; resting and post-prandial metabolic rates at 6 and 12 months of age; growth rates; pyramiding; and estimated body composition. Animals fed HS showed higher mass-specific intake of digestible energy (113.9 ± 32.1 kJ kg−1 day−1 vs. 99.6 ± 35.3 kJ kg−1 day−1; P < 0.05), digestible DM (6.1 ± 1.8 g kg−1 day−1 vs. 5.0 ± 1.8 g kg−1 day−1; P < 0.01), shorter transit (3 ± 1 days vs. 4 ± 1 days; P < 0.01) and retention times (8 ± 2 days vs. 10 ± 2 days; P < 0.01), and higher Da of DM, starch, NDF, and GE. Crude protein Da was higher for HF. Rest and post-prandial metabolic rates, and pyramiding degree were not affected by diets. At 13 months, the animals from HS presented wider plastrons and carapaces, and higher carapace width growth rates. In addition, these animals had lower body mineral content (1.88 ± 0.15% vs. 2.15 ± 0.19%; P < 0.01) and bone density (0.13 ± 0.01 g mm−2 vs. 0.15 ± 0.02 g mm−2; P < 0.02). Results provide evidence that highly digestible foods can accelerate shell growth and lower mineralization in this species.
Keywords: Body composition; Chelonoidis; Digestive response; Heat increment; Metabolic rate; Pyramiding